Identification of competency supervisor and technician heating ventilating and air conditioning (HVAC) maintenance in oil and gas industry Malaysia - Syazwan, M.M.S.; Yusop, F; Saad, M.S.; Sari, K.A. Mohd; Muhamad Damanhuri, Amir Abdullah; Hassan, N.N. Mat; Fahmi, A.R. (2023)
Heating Ventilation and Air Conditioning (HVAC) system is one of the critical systems which need to be maintained in oil and gas (O&G) industry Malaysia. HVAC system in O&G provide comfort for occupants and serve suitable ambient temperature for the critical rooms that are equipped with sensitive electrical equipment. The objective of this study is to identify the competency HVAC maintenance supervisor and technician in O&G industry Malaysia. The conceptual framework based on iceberg competency model have been used in this study to obtain technical, non-technical competency and core personality from the document. The result shows 17 competencies with 132 sub competencies for technical, 3 competencies with 38 sub competencies for non-technical and 4 competencies with 15 sub competencies for core personality. This identification of competency is an initial step to produce the competency framework for HVAC maintenance supervisor and technician O&G in the future.